Ukrainian national consensus on the examination and treatment of women after primary cervical screening - Н. А. Володько; А. Б. Вінницька; В. В. Камінський; Т. Ф. Татарчук; О. В. Попков; О. О. Білодід; Т. М. Боднар; А. В. Бойчук; Н. М. Волошина; І. Ю. Ганжий; Д. Г. Герман; О. Л. Жилко; et al. (Publishing House TRILIST, 2018)
This document is evidence of the uniting of the efforts of gynecologists and oncogynecologists of Ukraine in solving the problem of cervical cancer and can be considered as the first step towards the implementation of the global association program in the fight against this disease, put forward by the World Health Organization. Head of WHO Dr. Tedros Adhanom Ghebreyesus urged all countries to engage in this struggle and put an end to the suffering of cervical cancer. "Through cost-effective evidence-based interventions, including vaccination against human papillomavirus for girls, screening and treatment of precancerous lesions, improving access to diagnosis and treatment of invasive forms of cancer, we can eliminate cervical cancer as a public health problem and make it a disease of the past." This is the purpose of the recommendations of the Ukrainian National Consensus on the examination and treatment of women after primary cervical screening, which, of course, are not final - it will be improved and supplemented by annual consensus conferences and meetings. At the same time, the fight against cancer of the cervix must be widespread. It is important to involve family doctors and pediatricians in this struggle. In this regard, is necessary to introduce the topic "Primary and secondary prevention of cervical cancer - the path to the elimination of illness" in the curricula and programs of medical faculties of higher educational institutions of III-IV accreditation levels and postgraduate education. In addition, the opportunities of social networks and the media should be widely used to raise awareness of the population in the prevention of cervical cancer and to provide scientific evidence of the possibility of preventing this disease